Monodon monoceros (narwhal) - CFS-2187 - Moore, Michael J.; Taylor, David B. (Woods Hole Oceanographic Institution, 2022)
Monodon monoceros (narwhal) - CFS-2187 - female - unknown length - Pelvic location - Harvard University